A hydrophilic polyimidazolium antibiotic targeting the membranes of Gram-negative bacteria - Chen, Yahua (2024)
The rise of MDR Gram-negative bacteria (GNB), especially those resistant to last-resort drugs such as carbapenems and colistin, is a global health risk and calls for increased efforts to discover new antimicrobial compounds. We previously reported that polyimidazolium (PIM) compounds exhibited significant antimicrobial activity and minimal mammalian cytotoxicity. However, their mechanism of action is relatively unknown. We examined the efficacy and mechanism of action of a hydrophilic PIM (PIM5) against colistin- and meropenem-resistant clinical isolates.